Role of predictors in acceptance of post-exposure prophylaxis with single-dose rifampicin among contacts of leprosy in rural area of Bankura: An explanatory mixed-method study - Prianka Mukhopadhyay; Tanushree Karmakar; Aditya Prasad Sarkar; Sarkar, Manisha (Asian Journal of Medical Sciences, 2024)
Background: India achieved the elimination of leprosy two decades ago although its sustenance continues to be threatened by ongoing active transmission in few remaining pockets. There is a paucity of data regarding the acceptance of single-dose rifampicin (SDR) prophylaxis among healthy contacts. Aims and Objectives: The aims and objectives of the study are to assess the factors influencing the acceptability of SDR among contacts. Materials and Methods: A community-based, sequential, explanatory mixed-method study was conducted over 6 months from September 2022 to February 2023 among 168 contacts of leprosy patients from two blocks in Bankura district, West Bengal. Quantitative analysis was done for SDR acceptance and its predictors among contacts using the Chi-square test, Mann–Whitney U test, and Logistic regression. This was followed by qualitative assessment using focus group discussions and in-depth interviews among contacts to explain the findings through a thematic approach. Results: Household contacts (aOR=13.72, 95% CI=2.09–90.19), increasing knowledge score of contacts (aOR=3.18, 95% CI=1.88–5.38), counseling by health workers (aOR=11.98, 95% CI=2.20–65.15), trust in health workers (aOR=152.96, 95% CI=13.17–1776.09), and not taking other medicines for comorbidity (aOR=35.82, 95% CI=2.94–436.02) were associated with increased SDR uptake among leprosy contacts. Barriers and facilitators of post-exposure prophylaxis (PEP)-SDR were categorized as contact, health workers, and program-related factors. Conclusion: SDR acceptability among contacts was 77.4%. Facilitators of SDR-PEP were awareness of side-effects, follow-up, prompt support by health workers, IEC, belief in National programs, etc. Lack of knowledge of PEP-SDR and contraindications, ineffective counseling by health workers, stigma of the disease, the increased workload of health workers, etc., were the barriers to SDR-PEP implementation.